Aerospace series. Connectors, electrical, circular, coupled by threaded ring, fire-resistant or non fire-resistant, operating temperatures. 65°C to 175°C continuous, 200°C continuous, 260°C peak. Specification of performance and contact arrangements Part 002, (16th January 2023) - British Standards Institution,
No abstract available